2023
DOI: 10.35414/akufemubid.1145100
|View full text |Cite
|
Sign up to set email alerts
|

Serbest Formlu İnce Cidarlı AA 5083-H111 Alaşımının Frezelenmesinde Kesme Parametrelerinin Yüzey Pürüzlülüğü Üzerine Etkilerini Deneysel ve İstatiksel Değerlendirilmesi

Abstract: Bu çalışmada, kuru işleme koşullarında serbest formlu ince cidarlı AA 5083-H111 alaşımın kaplamasız karbür parmak freze ile işlenmesinde cidar kalınlığının, kesme hızının ve ilerleme miktarının yüzey pürüzlülüğü üzerindeki etkilerinin belirlenmesine odaklanmıştır. Ayrıca en düşük yüzey pürüzlülüğü için optimum kesme parametrelerinin belirlenmesinde Taguchi yöntemi ve regresyon analizi uygulanmıştır. Deney tasarımı Taguchi L32 (21x42) dizinine göre hazırlanmıştır. Deney ve analiz sonuçlarına göre, yüzey pürüzlü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The maximum surface roughness (Ra) is observed at a cutting speed of 15 m/min and a feed rate of 50 mm/min. It is generally observed that an increase in cutting speed during machining operations leads to a reduction in surface roughness (Akıncıoğlu et al, 2013a;Akkuş and Yaka, 2021;Özlü et al, 2023). This phenomenon can be attributed to the reduction in Fz at moderate cutting speeds, which has a beneficial impact on the surface roughness (Shapiro, 2009;Özlü, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The maximum surface roughness (Ra) is observed at a cutting speed of 15 m/min and a feed rate of 50 mm/min. It is generally observed that an increase in cutting speed during machining operations leads to a reduction in surface roughness (Akıncıoğlu et al, 2013a;Akkuş and Yaka, 2021;Özlü et al, 2023). This phenomenon can be attributed to the reduction in Fz at moderate cutting speeds, which has a beneficial impact on the surface roughness (Shapiro, 2009;Özlü, 2021).…”
Section: Resultsmentioning
confidence: 99%